2015
DOI: 10.5935/2446-4775.20150008
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos populares e científicos do uso de espécies deEugeniacomo fitoterápico

Abstract: O uso da biodiversidade brasileira pela população continua sendo uma das maiores fontes de descoberta de novas entidades químicas bioativas. Este trabalho realizou uma revisão da literatura referente às características botânica, etnobotânica, atividade farmacológica, toxicológica e constituição química das espécies de Eugenia: Eugenia brasiliensis Lam, Eugenia dysenterica DC, Eugenia umbelliflora O. Berg, Eugenia florida DC., Eugenia involucrate DC. e Eugenia uniflora L. Esse estudo descritivo retrospectivo te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
0
15
0
9
Order By: Relevance
“…Eugenia uniflora is one of the most investigated species of the Eugenia genus, including through botanical, phytochemical, and pharmacological studies, due to its wide geographic distribution [15]. In a previously published paper, we reported that the essential oil of a curzerene-rich E. uniflora chemotype showed a significant antiproliferative and cytotoxic effect against some cancer strains [16].…”
Section: Introductionmentioning
confidence: 99%
“…Eugenia uniflora is one of the most investigated species of the Eugenia genus, including through botanical, phytochemical, and pharmacological studies, due to its wide geographic distribution [15]. In a previously published paper, we reported that the essential oil of a curzerene-rich E. uniflora chemotype showed a significant antiproliferative and cytotoxic effect against some cancer strains [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is of prime 271 importance to inspect qualified individuals, traders, distributors and producers for 272 regularization of the sale of medicinal plants. Eucalyptus, are used by the population for this purpose and have antioxidant, antifungal 282 and antibacterial properties (Queiroz et al, 2015). Also, the natural environments to 283 which C. icaco occurs are restinga-type vegetation sites, which are usually areas of 284 environmental protection, which makes it difficult to collect specimens of this species.…”
Section: Cell Viability Assay 209 210mentioning
confidence: 99%
“…Dentre as espécies, é encontrado na forma de arbusto e de árvores, sua altura pode chegar de três a doze metros e possuir frutos de diversas colorações como amarelo, alaranjado, vermelho e preto (DE QUEIROZ, 2015).…”
Section: Pitangueira (Eugenia Uniflora L)unclassified